1980
DOI: 10.7326/0003-4819-92-4-471
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination in Kidney Transplant Recipients: Cellular and Humoral Immune Responses

Abstract: Influenza infection in renal transplant recipients may cause either morbidity and mortality or acute allograft rejection; thus, routine annual influenza vaccination should be considered. We have studied the humoral and cellular immune responses to influenza virus antigens before and after trivalent vaccine administration in 13 patients and 16 control subjects. The patients, nine of whom were either on alternate-day or low-dose daily steroid therapy, showed highly significant serum hemagglutination-inhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Three studies have shown normal antibody responses when compared to controls [10,23,24] while several others have described impaired immunogenicity [3,[17][18][19][20]25]. In two of the studies with normal antibody production, prednisone and azathioprine were the only immunosuppressants used.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies have shown normal antibody responses when compared to controls [10,23,24] while several others have described impaired immunogenicity [3,[17][18][19][20]25]. In two of the studies with normal antibody production, prednisone and azathioprine were the only immunosuppressants used.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy in immunodepressed individuals is described as adequate in renal and heart transplant recipients by some investigators. 47,67 Adult liver transplant recipients have also been reported to be adequately protected by the vaccine. In the study of Burbach et al, 65 protective postimmunization titers at 21 days for the 3 antigens contained in the vaccine (A/Bayern/07/95, A/Wuhan/359/95, and B/Bejing/ 184/93) were 92%, 92%, and 95% in liver transplant recipients compared with 97%, 100%, and 100% in healthy controls, respectively.…”
Section: Vaccinationmentioning
confidence: 99%
“…This event, although not well described in liver transplant recipients, is extensively documented after renal transplantation. [47][48][49][50] In the study of Mauch et al, 45 3 children with influenza had concurrent allograft rejection. Viruses other than influenza have been associated with the development of rejection in solid-organ transplant recipients.…”
Section: Risk For Influenza Infection In Patients After Liver Transplmentioning
confidence: 99%
“…Immune response in renal and heart transplant recipients has been described both adequate and impaired (2,9,13,16,98). Fraund et al vaccinated 79 heart recipients with the 1996/ 1997 trivalent vaccine.…”
Section: Influenza Vaccinementioning
confidence: 99%